Qualitative ultrasonography scale of the intensity of local twitch response during dry needling and its association with modified joint range of motion: a cross-sectional study - Cruz-Montecinos, Carlos; Cerda, Mauricio; Becerra, Pablo; Tapia, Claudio; Núñez-Cortés, Rodrigo; Latorre-García, Rodrigo; Freitas, Sandro R.; Cuesta-Vargas, Antonio (BMC Springer Nature, 2021)
Background: The relevance of local twitch response (LTR) during dry needling technique (DNT) is controversial, and it is questioned whether LTR is necessary for successful outcomes. Furthermore, because the LTR during the deep DNT may be evoked with different intensities, it is unknown whether the magnitude of LTR intensity is associated with optimal clinical results, especially concerning to the effects of joint maximal range of motion (ROM). This study aimed to (i) determine whether visual inspections can quantify the LTR intensity during the DNT through a qualitative ultrasonography scale of LTR intensity (US-LTR scale), and (ii) assess the differences of US-LTR scale associated with changes in the maximal joint ROM. Methods: Using a cross-sectional design, seven asymptomatic individuals were treated with DNT in the latent myofascial trigger point in both medial gastrocnemius muscles. During DNT, three consecutive LTRs were collected. The US-LTR scale was used to classify the LTRs into strong, medium, and weak intensities. The categories of US-LTR were differentiated by the velocity of LTRs using the optical flow algorithm. ROM changes in ankle dorsiflexion and knee extension were assessed before and immediately after DNT. Results: The US-LTR scale showed the third LTR was significantly smaller than the first one (p < 0.05). A significant difference in velocity was observed between US-LTR categories (p < 0.001). A significant difference in the ROM was observed between the strong and weak-medium intensity (p < 0.05). Conclusions: The present findings suggest that the LTR intensity can be assessed using a qualitative US-LTR scale, and the effects of DNT on joint maximal ROM is maximized with higher LTR intensity. This study reports a novel qualitative method for LTR analysis with potential applications in research and clinical settings. However, further research is needed to achieve a broader application.
Keywords: Ultrasonidos en medicina; Dry Needling; Local Twitch Response; Range of Motion; Trigger Points; Ultrasound